A pre-clinical animal study of a novel mechanical-only ablation device treatment for superficial venous disease. (March 2022) - Kabnick, Lowell S; Phelan, Nigel; Cummins, Seán; O Hynes, Seán
Objective: Current minimally invasive techniques for ablation in superficial venous reflux are limited to thermal based systems requiring tumescent anesthesia, non-thermal chemical sclerosants and permanent glue implantation. The aim of this feasibility study was to determine the safety and efficacy of a novel mechanical-only ablation (MOA) device called EnVena, in a recognised large animal model with chronic follow up. Methods: Venous ablation of six lateral saphenous veins in three sheep was performed using the EnVena device. Luminal patency and vein wall fibrosis were evaluated by histologic analysis at 51 and 89 days. Results: All treated veins demonstrated fibrotic occlusion in contiguous segments at 51 and 89 days on histological analysis. From 45 consecutive segments spanning the treatment length across the six treated veins, 26 (57%) were fully occluded, 7 (16%) were impinged or partially occluded and 12 (27%) were open. There were no device related complications during the follow up period. Conclusions: A purely mechanical approach to superficial venous ablation demonstrated safety and efficacy in a recognized large animal model based on histological findings.